2018
DOI: 10.1002/capr.12187
|View full text |Cite
|
Sign up to set email alerts
|

The talking cure—building the core skills and the confidence of counsellors and psychotherapists to work effectively with multilingual patients through training and supervision

Abstract: Background Increasing numbers of multilingual people seek counselling and psychotherapy in a system that is rooted in a monolingual ideology. Despite these numbers, there is very little training for therapists and counsellors equipping them to treat multilingual patients. This is strange given that therapeutic treatment is known as the “talking cure.” Research with therapists and counsellors about their beliefs and behaviour with multilingual patients revealed that therapists were anxious about their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
(55 reference statements)
3
22
0
Order By: Relevance
“…While examining the influence of the language of instruction in medical education is important, most of the language studies in the field have focused on the communication between the doctors and patients in the workplace environment. [4][5][6] The language of instruction in healthcare education has drawn the attention of only a few researchers around the globe and scholars have examined it in terms of graduate medical doctors in the United States and the United Kingdom 7 conducted a study on the use of English in the medical profession in the United States, the United Kingdom, and Australia and they encouraged the collaboration between applied linguists and medical professionals to support the needs of international medical students who speak English as a foreign language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While examining the influence of the language of instruction in medical education is important, most of the language studies in the field have focused on the communication between the doctors and patients in the workplace environment. [4][5][6] The language of instruction in healthcare education has drawn the attention of only a few researchers around the globe and scholars have examined it in terms of graduate medical doctors in the United States and the United Kingdom 7 conducted a study on the use of English in the medical profession in the United States, the United Kingdom, and Australia and they encouraged the collaboration between applied linguists and medical professionals to support the needs of international medical students who speak English as a foreign language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our knowledge, even if there is a focus on language in psychotherapy research, accounts predominantly examine the role of the client's multilingualism, but rarely the therapist's multilingualism, which may shape encounters with Language and Psychoanalysis, 2021, 10 (2), 1-22. http://dx.doi.org/10.7565/landp.v10i2.5542 5 multilingual/multicultural clients. Research has shown that awareness about multilingualism is crucial for therapists working with clients from different linguistic and cultural backgrounds (Bager-Charleson et al, 2017;Costa & Dewaele, 2019). The current qualitative study adds to this avenue of research by focusing on how multilingual and multicultural therapists in the Netherlands use their languages.…”
Section: Introductionmentioning
confidence: 95%
“…Many clients positioned the therapist as the gate‐keeper of linguistic practices, a finding which reinforces the need to train mental health practitioners to feel confident to offer a therapeutic space where multiple languages are welcome, where the exploration of clients’ linguistic histories is valued and where a multilingual therapeutic frame (Costa, 2020) is applied. Client feedback confirms that ‘talking about the talking’ (Costa & Dewaele, 2019) is productive and merits to be developed as a core skill for therapists.…”
Section: Resultsmentioning
confidence: 77%